Effect of styrene maleic anhydride on physical and mechanical properties of recycled polystyrene wood flour composites - Poletto, Matheus (Maderas. Ciencia y Tecnología, 2016)
In this work, the influence of three types of styrene maleic anhydride (SMA) oligomers on the adhesion of polystyrene wood plastic composites (WPC) was investigated. The composites were processed on a twin-screw co-rotating extruder below 200°C using 20 wt% of wood flour. The styrene maleic anhydride with different content of maleic anhydride groups, 30%, 25% and 20% (w/w) and levels of 1, 2 and 4% of coupling agents (styrene maleic anhydride 2000, styrene maleic anhydride 3000 and styrene maleic anhydride EF40) in the composite formulations were tested. Mechanical, physical and morphologic properties were evaluated. The styrene maleic anhydride improves the compatibility of hydrophilic wood flour with hydrophobic polystyrene matrix. It has been observed that the addition of styrene maleic anhydride increased the wood plastic composites mechanical properties with the incorporation of 2% wt of styrene maleic anhydride 2000. The mechanical properties showed to be dependent on content of maleic anhydride in the coupling agent. Treated and non-treated wood plastic composites showed similar density values, but the void content was reduced for treated composites. Scanning electron microscopy revel the better adhesion between polymer and matrix when coupling agent were used.